Perfil de pacientes com diabetes mellitus tipo I em tratamento através de sistema de infusão contínua de insulina em hospital de referência da Amazônia - SOUSA, Carlos Eduardo Santos de (2023)
Diabetes mellitus is an important and growing health problem for all countries, regardless of their degree of development. Diabetes Mellitus is characterized by increased hyperglycemia, caused by the lack of insulin or its inability to properly perform its function, leading to metabolic disorders. The main objective of research is to evaluate the glycemic and metabolic profile of type 1 diabetic patients using a continuous insulin infusion system (SICI) in a hospital health unit in the Amazon region. In the State of Pará, it has been implemented since 2019, the Continuous Insulin Infusion System (SICI) is seen as an alternative to the multiple daily application of insulin by diabetes patients, although it has numerous advantages, its availability in the public health system is still very low. Where, this is a retrospective, quantitative study with a descriptive approach. Regarding the results and discussions, a data collection was carried out at the diabetes clinic of the Endocrinology service of the Jean Bitar Hospital/CEDEPA, with a total of 83 patients, 79% of whom were SUS users, 55% were female, aged 26 years. .5±12.0 years, BMI of 23.0 ±7.2 kg/m² and T1DM diagnosis time of 13.7±9.2 years. Where they were tabulated and divided according to response and adaptation to treatment in glycated hemoglobin <7% and >7%. The present research also has a direct analysis regarding the patients and the main basic benefits of the use of the Continuous Infusion System of Insulin, where one of them is the ease of use, giving greater safety to the patient and above all, making the treatment more flexible. and its membership. Thus, it is concluded that the use of SICI is a great advance in the treatment of patients with DM, where patients with glycated hemoglobin <7%, partially obtained a better result in quality of care regarding DM and that SICI has evidence and direct efficacy with patients of different ages, also resulting in their quality of life.